Media Massa Melawan Teror: Analisis Framing pada Tajuk Koran Republika - Kun Wazis (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2017)
This study aims to describe the view of mass media with the Islamic ideology of Republika in response to mass shooting incident by Stephen Craig Paddock (64 years) in Las Vegas United States on Sunday (1/10/2017) which killed 59 people and injured 500 people. This research uses qualitative method with framing analysis of Robert Entman model which produces four important things. First, the editorial (header) entitled